Neuroleptics used in critical COVID associated with moderate-severe dyspnea after hospital discharge - Carlos Toufen; Gustavo Corrêa de Almeida; José Eduardo Pompeu; Celso Ricardo Fernandes de Carvalho; Carlos Roberto Ribeiro de Carvalho (Scientific Reports)
Abstract Dyspnea is a prominent symptom in patients with long COVID due to its high prevalence and significant clinical impact. However, the influence of commonly used medications in critically ill patients on long-term dyspnea remains unclear. This study aimed to identify risk factors and assess the impacts associated with moderate to severe dyspnea in COVID-19 survivors. This study evaluated patients admitted to a university hospital between April 2020 and April 2021. Data were collected on clinical preconditions, hospital and ICU stays, and the use of corticosteroids, neuroleptics, neuromuscular blockers, midazolam, fentanyl, and noradrenaline. Post-discharge evaluations were conducted at 1 and 12 months, assessing dyspnea, frailty, quality of life, functional capacity, anxiety, and depression. Descriptive statistics, including frequencies and percentages, were used, and logistic regression analysis was performed to identify factors associated with moderate to severe dyspnea at 1 and 12 months post-discharge. Statistical significance was defined as P < 0.05. A total of 100 patients were prospectively included in the study; all underwent the 1-month evaluation, and 63 completed the 12-month evaluation. Limiting dyspnea, defined as an mMRC score > 1, was observed in 56.6% of patients at 1 month and 33.9% at 12 months post-discharge. Independent factors associated with limiting dyspnea at 1 month included the total dose of neuroleptics administered during hospitalization and the presence of pre-existing comorbidities. The use of corticosteroids, neuromuscular blockers, midazolam, fentanyl, and noradrenaline showed no significant association with limiting dyspnea. Dyspnea at 1 month post-discharge was an independent risk factor for the persistence of limiting dyspnea at 12 months. Patients with limiting dyspnea at 12 months exhibited higher levels of depression, anxiety, and frailty, alongside reduced quality of life and functionality. Patients with severe COVID-19 exhibit a high prevalence of limiting dyspnea in the long term. The total dose of neuroleptics administered during hospitalization and the presence of comorbidities were independently associated with limiting dyspnea after discharge. At 12 months post-discharge, individuals with persistent limiting dyspnea frequently demonstrated additional physical and mental health impairments, underscoring the need for comprehensive evaluation and management to mitigate the burden of long-term disabilities.